SUCCESSFUL TREATMENT OF CUTANEOUS LEISHMANIASIS WITH INTRALESIONAL GLUCANTIME - Khan, Imranullah; Javed, Mohammad; Khan, Jahangir A (Journal of Ayub Medical College Abbottabad, 1996)
We performed a clinical trial to evaluate the efficacy and safety of intralesional glucantime in cutaneous leishmaniasis. Thirteen patients with cutaneous leishmaniasis were treated with intralesional glucantime using a 23-gauge needle. Each lesion was infiltrated with 1-2 ml of solution without local anaesthesia. Total number of injections was from 3 to 5, each one week apart. Resolution of the lesions was obtained in most of the patients (9 out of 13). The location and duration of the lesion did affect the outcome of treatment. The treatment was generally well tolerated. Intralesional treatment of cutaneous leishmaniasis is safe, effective and cheap, and excellent cosmetics results may be achieved.